2007
DOI: 10.1111/j.1439-0264.2007.00822.x
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic and Microscopic Anatomy of the Oviduct in the Sexually Mature Rhea (Rhea americana)

Abstract: The morphological characteristics of the oviduct of 12 sexually mature rheas (Rhea americana) were studied. Only the left oviduct is developed as a long tube with a length of 122 +/- 23.1 cm, and is subdivided into infundibulum (15.2 +/- 4.0 cm), magnum (63.3 +/- 9.4 cm), isthmus (5.6 +/- 3.1 cm), uterus (16.0 +/- 4.2 cm) and vagina (11.5 +/- 1.4 cm). The mucous membrane of the oviduct, as a whole, possesses luminal folds covered by ciliated columnar epithelium with secretory cells. The infundibulum part prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
14
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 9 publications
9
14
1
1
Order By: Relevance
“…They reported that the oviduct in all birds is attached to the celom by a thin double fold of dorsal and ventral oviductal ligaments. However, the current finding is contrary to the earlier reports of [29] in rhea bird, who divided the oviductal ligaments into three named ligaments according to the fixed region of the oviduct.…”
Section: Discussioncontrasting
confidence: 99%
“…They reported that the oviduct in all birds is attached to the celom by a thin double fold of dorsal and ventral oviductal ligaments. However, the current finding is contrary to the earlier reports of [29] in rhea bird, who divided the oviductal ligaments into three named ligaments according to the fixed region of the oviduct.…”
Section: Discussioncontrasting
confidence: 99%
“…The contractility of the tunica muscularis has been studied in the domestic fowl (Crossley et al, 1975) and Japanese quail (Talo and Kekalainen, 1976;Arjamaa and Talo, 1983). In the current study the arrangement of the layers forming the tunica muscularis was in agreement with previous studies on the avian oviduct (Hoffer, 1971;Sharma and Duda, 1989;Parizzi et al, 2008). As observed in the domestic fowl (Madekurozwa, 2013), the tunica muscularis of the Japanese quail was immunopositive for both desmin and SMA.…”
Section: Discussionsupporting
confidence: 92%
“…The morphology of infundibular glandular grooves and SST in the present study was similar to observations made in the domestic fowl (Burke et al, 1972), duck (Pal, 1977), Japanese quail (Frie et al, 1978), mallard (Sharma and Duda, 1989), rhea (Parizzi et al, 2008) and turkey (Bakst et al, 2010). The sperm storage capacities of both infundibular glandular grooves, as well as SST in the UVJ are well documented (Bobr et al, 1964;Bakst, 1981Bakst, , 1998Bakst, , 2011Bakst et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Diferente das aves (Parizzi et al 2008, os quelônios (Machado Júnior et al 2006, Chaves et al 2012) apresentam um par de ovários e ovidutos, ficando evidente em fêmeas adultas de M. vanderhaegei que a atividade ovariana é bilateral, devido a presença de pares de ovos nos ovidutos (útero) que correspondem a atividade dos ovários direto e esquerdo.…”
Section: Discussionunclassified